Serologic type conversion of a herpes simplex virus type 1 (HSV-1) to an HSV-2 epitope caused by a single amino acid substitution in glycoprotein C. - Kimmel, K A (1990)
A monoclonal antibody to herpes simplex virus type 2 glycoprotein C (gC-2) did not recognize wild-type herpes simplex virus type 1 gC (gC-1) but did recognize a mutant gC-1 molecule. This conversion from a type 1 to a type 2 epitope was shown to be due to a single amino acid substitution in gC-1.